Èquipe, community, traditional values, and reproductive rights - Corvino, Isabella; D'Andrea, Fabio (Frontiers in Sociology, 2023)
Gender stereotypes still surround women's reproductive health for several reasons. Moreover, in the last 20 years, women's access to essential reproductive healthcare is becoming an issue contributing to inequality and exacerbating different kinds of violence (cultural and structural). The patriarchal system, intimate partner violence, and traditional cultural and conservative values have a huge impact on women's access to contraceptive information, services, and induced abortion. Gender-based human rights violation has a higher impact on those women who are part of a minority or suffer a marginalized social or economic condition. In the present article, the behavior of migrant women's networks is examined as a case study when they come into contact with the health and care sector with the aim to highlight how, in the context of childbirth, they can suffer discriminatory and violent treatment by the community and groups that defend conservative and traditional values due to the exercise of reproductive rights. The investigated context was the Careggi Hospital in Florence, Italy, but in further investigation, the research will take place in different medium-sized cities such as Terni and Perugia. The chosen methodology was that of second-level sources and qualitative interviews with the health personnel who usually deals with these women (two focus groups involving 11 persons of the hospital équipe). This article has two aims: (1) to present the conflict between community behavior and the right to reproductive health and (2) to discuss aspects of IPV as degrading or violent treatment due to the exercise of reproductive rights. The main finding underlined the importance of considering the link between rights, identity, culture, and relationships with the community.